Contemporary Topics in Patient Safety - Volume 1 2022
DOI: 10.5772/intechopen.94108
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Reality Simulations in Nursing Education, and Patient Safety

Abstract: Nursing education puts theory into practice. Patient safety is indispensable in nursing education. During clinical practice, nursing students make medication errors and have difficulty deciding on what interventions to perform in unusual situations and communicating with patients or other healthcare professionals. All these problems put patient safety at risk. However, “First, do no harm” is a fundamental human right and an ethical principle, which nurses should always consider when they perform interventions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Virtual reality simulation with its ability to provide increased access and flexibility, 45 in particular, is useful in enabling students to practice for a longer duration and to acquire clinical skills that are not always experienced in the clinical setting 12 . Moreover, it is important to note that students who develop fundamental skills in virtual environments are more likely to consider patient safety in clinical practice 46 . Additional benefits beyond the development of skills were identified in a recent randomized controlled trial that found that VR promoted knowledge retention, clinical reasoning, self-efficacy, and greater satisfaction with the learning experience among nursing students 47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual reality simulation with its ability to provide increased access and flexibility, 45 in particular, is useful in enabling students to practice for a longer duration and to acquire clinical skills that are not always experienced in the clinical setting 12 . Moreover, it is important to note that students who develop fundamental skills in virtual environments are more likely to consider patient safety in clinical practice 46 . Additional benefits beyond the development of skills were identified in a recent randomized controlled trial that found that VR promoted knowledge retention, clinical reasoning, self-efficacy, and greater satisfaction with the learning experience among nursing students 47 …”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, it is important to note that students who develop fundamental skills in virtual environments are more likely to consider patient safety in clinical practice. 46 Additional benefits beyond the development of skills were identified in a recent randomized controlled trial that found that VR promoted knowledge retention, clinical reasoning, self-efficacy, and greater satisfaction with the learning experience among nursing students. 47 In a recent systematic review and meta-analysis by Woon et al, 10 VR was proposed as being suitable for supplementing conventional teaching and learning methods rather than being used as a standalone approach.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The use of realistic video simulations may have the potential to provide an experiential component to classroom learning. 12 Various studies have shown that using video simulation in the classroom can deepen students' understanding of classroom content and provide an additional learning mode to enhance classroom narrative. 7,13 In light of the literature, this study was conducted to determine the effect of the video-based simulated method on nursing students' motivation and academic achievement.…”
mentioning
confidence: 99%
“…The use of realistic video simulations may have the potential to provide an experiential component to classroom learning 12 . Various studies have shown that using video simulation in the classroom can deepen students' understanding of classroom content and provide an additional learning mode to enhance classroom narrative 7,13 .…”
mentioning
confidence: 99%
“…Immersive virtual reality (VR) as a teaching modality provides a three-dimensional platform the allows the end user to feel present and interact with a virtual world (Chen et al, 2020; Mendez et al, 2020). Evidence demonstrates that active engagement enables deep understanding, increases learning retention, motivates students, and builds confidence (Bayram & Caliskan, 2020; Foronda et al, 2017; Hardie et al, 2020). Advances in technology make VR available and affordable, providing nurse educators a powerful tool to augment and enhance clinical learning (Mendez et al, 2020).…”
mentioning
confidence: 99%